A Design of Environmental Education for Secondary School Teachers - Hidayatullah Hidayatullah; Kheryadi Kheryadi (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2020)
The focus of this research was to develop a system of environmental education (EE) skills development for secondary school teachers, which was carried out using qualitative approaches. The data were obtained by the Eco-School Operational Teachers Questionnaire and a standardized interview with the experts of the Eco-School Teachers and the Eco-School Teachers. Results of this study showed that the majority of informants had an intermediate level of EE competence in 6 parts: environmental awareness, basic understanding of EE, responsibility for EE instructor updating, EE preparation and service, support for EE learning, and EE assessment. The EE development was produced to cultivate educators out of a variety of subjects to carry out interoperable learning in order to improve the environment of students before preserving or resolving society environmental issues. This systematically consisted of 5 steps including: analyzing the environmental policy covering national, educational area, and school policies; studying the community environmental problem; designing the environmental learning project; identifying the learning standard; and performing the integrated lesson plan. Authentic assessment has confirmed the efficiency of innovation, both internal and external skills